Electrochemical ammonia synthesis through N2 and H2O under ambient conditions: Theory, practices, and challenges for catalysts and electrolytes. (March 2020) - Xu, Hui; Ithisuphalap, Kemakorn; Li, Yi; Mukherjee, Shreya; Lattimer, Judith; Soloveichik, Grigorii; Wu, Gang
Abstract: Due to its high energy density, carbon-free character, and the convenience for storage and transportation, ammonia (NH3 ) is considered as an energy vector, capable of being used for energy storage and directly as a fuel. Increasing demands for ammonia have necessitated the development of alternative synthesis approaches as the backup technology to the energy-intensive Haber-Bosch process. Among others, the electrosynthesis of ammonia (ESA) technology offers a promising approach to produce NH3 via a cathodic nitrogen reduction reaction (NRR). However, current ESA technologies desperately suffer from insufficient production rates (<10 −6  mol h −1  cm −1 ) and low Faradaic efficiency (<30%) due to the lack of highly active and selective NRR catalysts and favorable electrolytes to suppress competitive hydrogen evolution reaction. This review provides an insight into the ESA technology with an emphasis on the design of catalyst/electrolyte systems that optimizes the production of NH3 from N2 and H2 O under ambient conditions. Basic electrochemical principles and reaction mechanisms of the NRR are briefly analyzed in the first section, followed by the impacts of electrochemical components ( e.g ., catalysts and electrolytes) that define the effectiveness of EAS technologies. The challenges that limited the developments and the approaches that researchers have focused on the catalyst developments are discussed in detail with the main emphasis on the combined catalyst/electrolyte systems. Finally, NRR performance evaluation methods, along with economic analysis of the EAS, are critically examined. Graphical abstract: Image 1 Highlights: The electrosynthesis of ammonia (ESA) technology offers a promising approach to produce NH3 via H2 O and N2 . The review provides an insight into the ESA technology with an emphasis on the synergy of catalysts and electrolytes. Basic electrochemical principles and reaction mechanisms of NRR are examined. Current challenges and future research directions are outlined.